Analysis of Blended Learning Model on Digital Literacy Skills - Sari, Maya; Muntholib, Muntholib; habiddin, Habiddin; Sumari, Sumari; Rahayu, Sri (Journal of Disruptive Learning Innovation (JODLI), 2024)
Blended learning is the same as hybrid learning, which combines the concept of traditional school teaching with online learning through personalized instruction for an entire group of students. The Systematic Literature Review follows the structure of the PRISMA framework (Preferred Reporting Items for Systematic Review and Meta Analysis). The literature search was carried out in the web database eric.go.ed under the keyword “Digital Literacy”. Based on the extraction, 40 articles were selected for analysis. The following results were obtained: (1) The research trend on the impact of digital skills on blended learning is still dominated by the social science field; (2) The inclusion of digital devices in blended learning is dominated by the use of LMS (Learning Management System); several studies have reported combining the use of LMS with metaverse devices such as augmented reality; (3) The analysis of the differences in digital skills before and after the Covid-19 pandemic can be seen based on the use of digital platforms.